A Thin Layer of Decellularized Porcine Myocardium for Cell Delivery. Issue 1 (December 2018) - Shah, Mickey; KC, Pawan; Copeland, Katherine; Liao, Jun; Zhang, Ge
Abstract Decellularized porcine myocardium has shown many benefits as a cell delivery scaffold for cardiac therapy. However, using full thickness decellularized myocardium as cardiac patch may lead to poor viability and inhomogeneous distribution of delivered cells, due to perfusion limitations. In this study, we explored the feasibility of decellularized porcine myocardial slice (dPMS) to construct a vascularized cardiac patch for cell delivery. Decellularized porcine myocardium was sliced into thin layers (thickness 300 µm). Adipose-derived Stem cells (ASCs) obtained from rat and pig were seeded on dPMS. The viability, infiltration, and differentiation of seeded ASCs were examined. The mechanical properties of dPMSs of various thickness and native myocardium were tested. We noticed dPMS supported attachment and growth of rat and pig ASCs. Both rat and pig ASCs showed high viability, similar patterns of proliferation and infiltration within dPMS. Rat ASCs showed expression of early-endothelial markers followed by mature-endothelial marker without any additional inducers on dPMS. Using rat myocardial infarction model, we delivered ASCs using dPMS patched to the infarcted myocardium. After 1 week, a higher number of transplanted cells were present in the infarcted area when cells were delivered using dPMS versus direct injection. Compared with MI group, increased vascular formation was also observed.